2013
DOI: 10.1007/s00441-013-1630-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of isolation methodology on stem cell properties and multilineage differentiation potential of human dental pulp stem cells

Abstract: Dental pulp stem cells (DPSCs) are an attractive alternative mesenchymal stem cell (MSC) source because of their isolation simplicity compared with the more invasive methods associated with harvesting other MSC sources. However, the isolation method to be favored for obtaining DPSC cultures remains under discussion. This study compares the stem cell properties and multilineage differentiation potential of DPSCs obtained by the two most widely adapted isolation procedures. DPSCs were isolated either by enzymati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
171
0
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 196 publications
(196 citation statements)
references
References 39 publications
10
171
0
7
Order By: Relevance
“…29 This technique is based on the outgrowth of cells from small tissue fragments, and it allows the isolation of a relatively pure population of pulp stem cells. 19 However, a heterogeneous population of cells, achieved with the enzymatic technique, is needed in some cell-based therapy approaches, since it can endure various environmental signals within the tissue 29 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…29 This technique is based on the outgrowth of cells from small tissue fragments, and it allows the isolation of a relatively pure population of pulp stem cells. 19 However, a heterogeneous population of cells, achieved with the enzymatic technique, is needed in some cell-based therapy approaches, since it can endure various environmental signals within the tissue 29 .…”
Section: Discussionmentioning
confidence: 99%
“…18 Few studies have compared the enzymatic and explant techniques for DPSCs isolation. 23,29,31 In a well-designed study, Hilkens and collaborators showed that cells isolated by the enzymatic or the explant techniques had the same proliferating rate and colony formation capacity, and could successfully differentiate into adipogenic, chrondrogenic and osteogenic cell types, indicating that both isolation methodologies could be applied to obtain suitable autologous DPSCs. 29 One particular aspect of the explant technique is the size of tissue fragments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two methods are used to perform the isolation of mesenchymal stem cells 13 : 1) Enzymatic digestion; 2) Primary culture or Explant…”
Section: Isolation Methods For Stem Cellsmentioning
confidence: 99%
“…enzymes could be aggressive towards these cells. However, both techniques are considered adequate for obtaining stem cells 13 . Once an adequate amount of cells has been obtained, they can be used in SC-BT or safely frozen either in liquid nitrogen for up to 2 years or in a freezer at -80ºC for up to one year 4 .…”
Section: Isolation Methods For Stem Cellsmentioning
confidence: 99%